Involvement of Cyclooxygenase- and Lipoxygenase-Mediated Conversion of Arachidonic Acid in Controlling Human Vascular Smooth Muscle Cell Proliferation - Brinkman, Herm-Jan M; Buul-Worteiboer, Marijke F van; Mourik, Jan A van (Thrombosis and Haemostasis, 1990)
We observed that the growth of human umbilical arterysmooth muscle cells was inhibited by the phospholipase A2 inhibitors p-bromophenacylbromide and mepacrine. Thesefindings suggest that fatty acid metabolism might be integrated in the control mechanism of vascular smooth muscle cell proliferation. To identify eicosanoids possibly involved in this process, we studied both the metabolism of arachidonic acid of these cells in more detail and the effect of certain arachidonic acid metabolites on smooth muscle cells growth. We found no evidence for the conversion of arachidonic acid via the lipoxygenase pathway. In contrast, arachidonic acid was rapidly converted via the cyclooxy-genase pathway. The following metabolites were identified: prostaglandin E2 (PGE2), 6-keto-prostaglandin F1α (6-k-PGF1α), prostaglandin F2α (PGF2α), 12-hydroxyheptadecatrienoic acid (12-HHT) and 11-hydroxyeicosatetetraenoic acid (11-HETE). PGE2 was the major metabolite detected. Arachidonic acid metabolites were only found in the culture medium, not in the cell. After synthesis, 11-HETE was cleared from the culture medium. We have previously reported that PGE2 inhibits the serum-induced [3H]-thymidine incorporation of growth-arrested human umbilical artery smooth muscle cells. Here we show that also 11-HETEexerts this inhibitory property. Thus, our data suggeststhat human umbilical artery smooth muscle cells convert arachidonic acid only via the cyclooxygenase pathway. Certain metabolites produced by this pathway, including PGE2 and 11-HETE, may inhibit vascular smooth muscle cell proliferation.